Performance and Productivity of Local Chicken Cross Third Generation At Age 1 to 10 Weeks - H Nurcahya; S Darwati; I.J. Tambunan (Universitas Nasional Jakarta, 2020)
Local chickens had some advantages such as high adaptability and resistance to disease, so they can be raised in remote rural areas. However, there are several drawbacks including the relatively slow growth. One way to overcome these weaknesses is by conducting cross-breeding and selection so that the productivity of chickens can increase. The aim of this research was to evaluate the product of crossbreeding between SkkeduxkeduSK and SkkeduxkeduSK chickens. The chickens used in this research were 43 DOC SKkeduxkeduSK and 46 KeduSKxSKkedu DOC. This research used T test was to determine the difference in average body weight, feed consumption, feed conversion and mortality from crosses between kedu chickens and sentul-kampung chickens. Crossbreeding between SkkeduxkeduSK and SkkeduxkeduSK chickens. The feed given was in 3 phases: 1) 100% commercial feed for 0-3 week old chickens, 2) 80% commercial feed mixed with 20% rice bran for 4 week old chickens and 3) 60% commercial feed mixed with 40% rice bran for 5-10 week old chickens.The variables measured included body weight, feed consumption, feed conversion and mortality. between SKkeduxkeduSK and KeduSKxSKkedu were not significantly different. SKkeduxkeduSK and KeduSKxSKkedu chickens had the same growth. The body weight of crossbreeding between SKkeduxkeduSK and keduSKxSKkedu reached 0.8 – 0.9 kg at the age 10 week. SKkeduxkeduSK and keduSKxSKkedu chickens were quite efficient in the use of feed with a conversion value of 3.0-3.7. But the mortality on this crossbreeding chickens was still quite high as it reached 3% in the population.